HEALTH INTERVENTION ON DECREASING ELDERLY DEPRESSION: REVIEW ARTICLE - Afni, Erina Nur; Nugraheni, Sri Achadi (JOURNAL OF RESEARCH IN PUBLIC HEALTH SCIENCES, 2019)
Growth of 20-25% prevalence of psychiatric disorders in Iran compared to 21.5% in 2012(1) damage to health, happiness, ability to carry out daily activities(2) and cause 50% of psychosomatic disorders. So that 30% of people referred to the health center suffer from psycho-socio-spiritual problems (1). The inclusion of the spiritual health dimension into the concept of health, introduces an important dimension, for health experts(3). "The Copenhagen Declaration on Social Development" and the "Bangkok Charter" emphasize the spiritual dimension for recent health promotion(4). "The International Nursing Council" finds the role of nurses in promoting an atmosphere in which human rights, values, habits, and spiritual beliefs of people, families and communities are respected.